2005
DOI: 10.1121/1.1928807
|View full text |Cite
|
Sign up to set email alerts
|

Empirical modeling of human face kinematics during speech using motion clustering

Abstract: In this paper we present an algorithm for building an empirical model of facial biomechanics from a set of displacement records of markers located on the face of a subject producing speech. Markers are grouped into clusters, which have a unique primary marker and a number of secondary markers with an associated weight. Motion of the secondary markers is computed as the weighted sum of the primary markers of the clusters to which they belong. This model may be used to produce facial animations, by driving the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Contrary to empirical models based on recorded data or medical images (for example Lucero et al (2005) or Badin et al (2008)), our approach in the last decade has been to develop biomechanical models of speech articulators, which are as close as possible to the human anatomy and functional morphology. Special emphasis has been given to the representation of the muscular structures and the rheological properties of soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to empirical models based on recorded data or medical images (for example Lucero et al (2005) or Badin et al (2008)), our approach in the last decade has been to develop biomechanical models of speech articulators, which are as close as possible to the human anatomy and functional morphology. Special emphasis has been given to the representation of the muscular structures and the rheological properties of soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Experiment 1 was designed to establish that perceivers in fact selectively attend to the lip movements of the model speaker during visual vowel discrimination tasks that elicit perceptual biases. Detailed analyses of intramuscular recordings and kinematic data indicate that visible speech movements are spatially distributed across the whole face (e.g., Vatikiotis-Bateson, Munhall, Kasahara, et al, 1996; Vatikiotis-Bateson, Munhall, Hirayama, Lee, & Terzopolous, 1996; Munhall & Vatikiotis-Bateson, 2004; Lucero & Munhall, 1999; Lucero, Maciel, Johns, & Munhall, 2005). Furthermore, perception studies using eye-tracking methodology indicate that perceivers frequently gaze at facial regions that extend beyond the lips while they watch and listen to a speaker talk (e.g., Vatikiotis-Bateson, Eigsti, Yano, & Munhall, 1998; Paré, Richler, ten Hove, & Munhall, 2003; Everdell, Marsh, Yurick, Munhall, & Paré, 2007; Irwin & Brancazio, 2014).…”
mentioning
confidence: 99%
“…While slower modulations were not found in the analysis of the GRID data, the GRID data revealed a number of more detailed orofacial components. Decomposition of the face during speech has been pursued in previous work using PCA [ 18 , 19 , 37 ], ICA [ 79 ] or other matrix factorization algorithms [ 38 , 40 ]. Lucero et al (2008) identified independent kinematic components for the upper and lower parts of the mouth and the two mouth corners, that were also identified in our AV analysis of the GRID data [ 40 ].…”
Section: Discussionmentioning
confidence: 99%